2006
DOI: 10.14358/pers.72.3.269
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphometry from SRTM

Abstract: The Shuttle Radar Topography Mission (SRTM) produced near-global 1Љ and 3Љ DEMs. The cartographically-derived National Elevation Dataset (NED) provides a mechanism to assess SRTM quality. We compared 12 geomorphometric parameters from SRTM to NED for about 500,000 sample areas over the continental United States. For basic parameters like average elevation or relief, the two data sets correlate very highly. For more derived measures, such as curvature and higher moments (skewness and kurtosis), the correlations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(72 citation statements)
references
References 16 publications
2
70
0
Order By: Relevance
“…Rivers present only a minor portion of the cells in a DEM, but this portion is particularly prone to certain types of errors (Guth, 2006;McMaster, 2002). Elevation anomalies along the valley bottoms of the Pieniny Mountains in Poland were found to range from −39 to +145 m in the X-band SRTM and in the ASTER GDEM from −52 to +88 m (Czubski et al, 2013;Ludwig and Schneider, 2006), thus vastly exceed-ing reported DEM accuracies (Jarvis et al, 2008;Tachikawa et al, 2011).…”
Section: Dem Artifacts and The Longitudinal River Profilementioning
confidence: 99%
“…Rivers present only a minor portion of the cells in a DEM, but this portion is particularly prone to certain types of errors (Guth, 2006;McMaster, 2002). Elevation anomalies along the valley bottoms of the Pieniny Mountains in Poland were found to range from −39 to +145 m in the X-band SRTM and in the ASTER GDEM from −52 to +88 m (Czubski et al, 2013;Ludwig and Schneider, 2006), thus vastly exceed-ing reported DEM accuracies (Jarvis et al, 2008;Tachikawa et al, 2011).…”
Section: Dem Artifacts and The Longitudinal River Profilementioning
confidence: 99%
“…The original 1" SRTM data follows the observations made by Guth (2006), and plots almost atop the curve for the simulated 2" NED, while the original 1" NED plots far to right (higher mean slopes). The curve for 3" SRTM data plots far to the left (lower mean slopes), accompanied by the interpolated 1"-IDW data, which shows that inverse distance weighted resulted in an underestimation of slopes, thus it should not be used to resample DEMs to higher resolutions.…”
mentioning
confidence: 51%
“…This parameter not only influences the smoothness of the kriged surface, but also strongly determines the computational time involved, since the size of covariance matrices grows up exponentially. According to Guth (2006), SRTM 1" data compares much more closely with simulated 2" NED than with 1" NED. Following his methodology, we created a simulated 2" NED DEM by decimating the 1" data and used a plot of mean slope value versus elevation to compare the DEMs in this study.…”
mentioning
confidence: 94%
“…The exceptional value of SRTM3 is due to great geographical coverage, consistency and detail. This 3-s collection is based on the original 1-s terrain model (GUTH 2006). When the SRTM data set was created, there already existed a less detailed model GTO-PO30, which was developed primarily on the basis of maps (detail of 30 s or 1 km).…”
Section: Source Datamentioning
confidence: 99%